Strategies for Overcoming Al Qur'an Enlightenment in Children Through Real Work College Programs - Elfi Yanti Ritonga; Ali Hasnan Batubara; Fadilla Ummi; Alya Dina (Tarbiyah Departement collaboration with AMCA, 2023)
This study aims to obtain accurate information about the causes of illiteracy in the village of Manyabar, Panyabungan sub-district and the strategies of UINSU students to overcome illiteracy. This research is descriptive qualitative research. According to Sugiyono, as quoted by Salim and Haidir, qualitative research is research aimed at understanding social phenomena from the participant's point of view. Respondents in this study were students in Manyabar Village, totalling 30 children (12 men and 18 women). The research was conducted for one month, starting from June 18 to August 18, 2022. The results of this study found that the factors causing the occurrence of the Al-Qur'an script in the village of Manyabar, Panyabungan sub-district, were among others due to economic factors and lack of a supportive environment. The strategy is by using various methods and using a curriculum that refers to the competence of students; evaluation is by measuring the level of ability of students both in terms of writing, reading and listening, which UINSU students then give an assessment.